Genetic Analysis of Rice (Oryza sativa L.) Genotypes Under Wet Direct Seeding Condition - Srinivas, B.; Chandramohan, Y.; Padmaja, D.; Thippeswamy, S.; Laxman, S. (International Journal of Bio-resource and Stress Management, 2023)
Present investigation was carried out with 35 rice genotypes under wet direct seeding condition at Regional Agricultural Research Station, Jagtial, PJTSAU, Telangana, India during kharif (June to October), 2016. High GCV and PCV values for important yield contributing traits viz., 1000 grain weight (24.41, 24.62) and number of grains panicle-1 (26.17, 29.30) were observed. High heritable and genetic advance values for 1000 grain weight (98.30, 49.86) and number of grains panicle-1 (79.80, 48.16) indicated the role of additive genes and these traits can be improved by simple selections. Effective bearing tillers m-2recorded low values of heritability (25.40) and genetic advance (5.19) suggesting the exploitation of heterosis for improvement of this important yield character. Effective bearing tillers m-2 (0.7097**), plant height (0.5014**) and panicle length (0.3219**) exhibited significant correlations with yield, hence direct selection for these traits could improve the yield. Highest inter cluster distance was observed between clusters IV and VI (27.75) followed by III and VI (24.69), IV and V (22.34) and III and V (22.23) thus high heterotic hybrids can be developed by making crosses between genotypes of the clusters. 1000 grain weight (44.2%) contributed highest towards total divergence followed by days to 50% flowering (40.17%) and plant height (10.76). Genotypes from cluster V and VI can be used as parents in breeding programme for development of extra early varieties. Cluster II and IV recorded lowest means for plant height and hence genotypes from these clusters can be used as parents for development of dwarf varieties desirable for wet direct seeding condition.